Korsfibler af Råhedetypen – En upåagtet fibeltype fra ældre vikingetid - Feveile, Claus (Kuml, 2011)
Crucialform fibulas of Råhede type An overlooked fibula type from the Early Viking Age Metal-detector archaeology has had astonishing consequences for our understanding of, in particular, the metal artefacts of the Late Iron Age. Completely new types have turned up, regional differences in others have become evident, unique specimen after unique specimen has seen the light of day, while other types stereotypically have been found time and again. In Denmark and Norway, a number of cruciform fibulas have been found, particularly during the last five years (figs. 1-2). The great majority of these are metal-detector finds with no associated context or date, but a few have been found during excavations of graves (no. 3) or market places (nos. 1 and 17). To date, there are 18-19 known examples, of which half are from Southern Jutland with a clear emphasis in the area close to Ribe. There is a single example from Kaupang in Norway whereas, surprisingly, none have been found at Haithabu in Southern Schleswig, despite the frequent metal-detector surveys here in recent years. Surprisingly, because there is normally great similarity between the find types seen at Haithabu and in the Ribe area. Cruciform fibulas of Råhede type are modelled on Carolingian brooches of the 9th century, but should doubtless be perceived as locally manufactured ornaments with Christian symbolism dating from the middle and late 9th century. Accordingly, they are an important factor in the discussion of when, how and where Christianity made its breakthrough in Denmark. Claus Feveile Museum Sønderjylland